Biodiesel from the waste cooking oil is catalyzed by egg-shell of purebred chicken with methanol as a solvent - Priska Marisa Pattiasina; I Wayan Sutapa; Hellna Tehubijuluw (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2023)
The synthesis of biodiesel from the waste cooking oil was carried out using the catalyst from egg shell of purebred chicken with methanol as a solvent. Synthesis the biodiesel was prepared in two steps, there are esterification and transesterification. In esterification was conducted in mol ratio of methanol and waste cooking oil were 9:1, with H2SO4 as a catalyst. Transesterification with mol ratio methanol and waste cooking oil were 12:1, with CaO from egg shell of purebred chicken as a catalyst. CaO catalyst was yielded by calcinations egg shell of purebred chicken on 1000 ⁰C for two hours. Calcination product was characterized with X-RD to determine of CaO. Result of biodiesel was characterized based on 1H-NMR, FTIR, GC-MS, dan ASTM (American Standard Testing of Materials). Yielded of biodiesel theoretically was 40.298% and experiment was 36.779%. Main component that resulted there is methyl stearic (40.21%).